Automatic temperature control fan / Mohammad Ikmal Abdul Rahman, Abdullah Aqil Mohd Amin and Faiz Izzuddin Johari - Abdul Rahman, Mohammad Ikmal; Mohd Amin, Abdullah Aqil; Johari, Faiz Izzuddin (2013)
The automatic temperature control fan was selected among the three idea for this project. The project was selected due to the availability of society to use it. This project help society by reducing the energy consumption in their daily life, making their life simpler. In our project consist of two circuit which are sensor circuit and voltage regulator circuit. The idea of using voltage regulator is to be used in household. The voltage regulator decreases AC 240 volt to DC 12 volt. Then the voltage will go through sensor circuit and activate it. In sensor circuit, there is thermistor that will react instantly based on the surrounding temperature.